Application of the Integration of Boppps Teaching Model and Ideological and Political Education in Preschool Hygiene Education - Lan, Lan; Cheng, Shijie (Transactions on Social Science, Education and Humanities Research, 2024)
In the context of modern educational development, exploring effective teaching methods to cultivate preschool education talents with comprehensive qualities is particularly important. This study aims to explore the application and effects of integrating the BOPPPS teaching model with Ideological and Political Education in the teaching of preschool hygiene. Through a combination of literature review and empirical research, we adopted a teaching design that integrates the BOPPPS model with Ideological and Political Education and implemented a teaching experiment. After the course ended, the experimental group's final total scores and practical assessment scores were significantly better than the control group, and the scores for humanistic care were also significantly better than the control group, with differences being statistically significant. The questionnaire on the effectiveness of Ideological and Political Education showed positive results. The results indicate that combining the BOPPPS teaching model with Ideological and Political Education helps improve students' academic performance and enhances teaching effectiveness. Its application in the teaching of preschool hygiene has proven feasible, providing an innovative teaching strategy for preschool hygiene education.